The Significance of Trust as A Key Predictor of Social Capital - Mukhammadiyeva Sh. G (American Journal Of Social Sciences And Humanity Research, 2025)
The article considers some theoretical approaches to defining the concepts of "social capital" and "trust", analyzes the sources, functions of social capital and its differences from other forms of capital, the role of trust in the structure of social capital, and the cultural foundations of this phenomenon. In addition, methods of measuring trust in world experience are discussed. The article also includes an analysis of the results of a trust survey.